The Joint-Specific BACH classification: A predictor of outcome in prosthetic joint infection. (December 2021) - Hotchen, Andrew James; Wismayer, Martina Galea; Robertson-Waters, Eve; McDonnell, Stephen M.; Kendrick, Ben; Taylor, Adrian; Alvand, Abtin; McNally, Martin
Abstract: Background: There is currently no commonly accepted method of stratifying complexity of prosthetic joint infection (PJI). This study assesses a new classification, the Joint-Specific, Bone involvement, Anti-microbial options, Coverage of the soft tissues, Host status (JS-BACH) classification, for predicting clinical and patient reported outcomes in PJI. Methods: Patients who received surgery for PJI at two centres in the UK between 2010 and 2015 were classified using JS-BACH as 'uncomplicated', 'complex' or 'limited treatment options'. Patient reported outcomes were recorded at 365-days following the index operation and included the EuroQol EQ-5D-3L index score and the EQ-visual analogue score (VAS). Clinical outcome data were obtained from the most recent follow-up appointment. Findings: 220 patients met the inclusion criteria. At 365-days following the index operation, patients with 'uncomplicated' PJI reported similar EQ-index scores (0.730, SD:0.326) and EQ-VAS (79.4, SD:20.9) compared to the age-matched population. Scores for 'uncomplicated' PJI were significantly higher than patients classified as having 'complex' (EQ-index:0.515 SD:0.323, p = 0.012; EQ-VAS:68.4 SD:19.4, p = 0.042) and 'limited treatment options' PJI (EQ-index:0.333 SD:0.383, p < 0.001; EQ-VAS:60.2, SD:23.1, p = 0.005). The median time to final follow-up was 4.7 years (inter-quartile range 2.7–6.7 years) where there were 74 cases (33.6%) of confirmed recurrence. Using death as a competing risk, the Cox proportional-hazards ratio of recurrence for 'complex' versus 'uncomplicated' PJI was 23.7 (95% CI:3.23–174.0, p = 0.002) and having 'limited options' verses 'uncomplicated' PJI was 57.7 (95% CI:7.66–433.9, p < 0.001). Interpretation: The JS-BACH classification can help predict likelihood of recurrence and quality of life following surgery for PJI. This will aid clinicians in sharing prognostic information with patients and help guide referral for specialist management of PJI. Funding: Data acquisition was funded by the National Institute for Health Research (NIHR), Trials No. ISRCTN91566927 . AJH is funded by a Versus Arthritis clinical research fellowship. ERW is funded by a national institute of health research (NIHR) academic clinical fellowship. SMM and AA are funded by a NIHR University lectureship.